Creation/destruction of ultra-wide binaries in tidal streams - Peñarrubia, Jorge (Monthly notices of the Royal Astronomical Society, 2021)
ABSTRACT This paper uses statistical and N-body methods to explore a new mechanism to form binary stars with extremely large separations (${\gtrsim}0.1\, {\rm pc}$), whose origin is poorly understood. Here, ultra-wide binaries arise via chance entrapment of unrelated stars in tidal streams of disrupting clusters. It is shown that (i) the formation of ultra-wide binaries is not limited to the lifetime of a cluster, but continues after the progenitor is fully disrupted, (ii) the formation rate is proportional to the local phase-space density of the tidal tails, (iii) the semimajor axis distribution scales as p(a)da ∼ a1/2da at a ≪ D, where D is the mean interstellar distance, and (vi) the eccentricity distribution is close to thermal, p(e)de = 2ede. Owing to their low binding energies, ultra-wide binaries can be disrupted by both the smooth tidal field and passing substructures. The time-scale on which tidal fluctuations dominate over the mean field is inversely proportional to the local density of compact substructures. Monte Carlo experiments show that binaries subject to tidal evaporation follow p(a)da ∼ a−1da at a ≳ apeak, known as Öpik’s law, with a peak semimajor axis that contracts with time as apeak ∼ t−3/4. In contrast, a smooth Galactic potential introduces a sharp truncation at the tidal radius, p(a) ∼ 0 at a ≳ rt. The scaling relations of young clusters suggest that most ultra-wide binaries arise from the disruption of low-mass systems. Streams of globular clusters may be the birthplace of hundreds of ultra-wide binaries, making them ideal laboratories to probe clumpiness in the Galactic halo.